From Superman to Super Jesus: Constructions of Masculinity and Disability on the Silver Screen - Schumm, Darla; Koosed, Jennifer L. (Disability Studies Quarterly, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->One of the dominant images of Jesus emerging in the late twentieth and early twenty-first centuries is that of the Super Jesus. Building on the hyper-masculinity of the American superhero, the recent portrayals of Jesus in Mel Gibson’s The Passion of the Christ and Philip Saville’s The Gospel of John demonstrate how the figure of Jesus is often represented as a Super Jesus – strong, impervious to pain, ultimately triumphant. In these movies, Jesus' body is subjected to extreme violence and yet he is able to control and transcend his broken body both before and after death. Drawing on the work of disability scholars both in and outside of religious studies, this paper argues that the model of the Super Jesus constructs an ideal of masculinity that prevents the exploration of alternative theologies of disability, alternatives that present different understandings of Incarnation, resurrection, and heaven.